Variable stiffness foot design and validation. (9th June 2021) - Lecomte, Christophe; Ármannsdóttir, Anna Lára; Starker, Felix; Tryggvason, Heimir; Briem, Kristin; Brynjolfsson, Sigurður
Abstract: Energy storing and returning prosthetic feet are commonly prescribed. Research has demonstrated advantages to use these types of prosthetic feet. However, their stiffness in the sagittal plane is fixed and cannot adapt to different walking tasks and user preference. In this paper, we propose a novel prosthetic foot design capable of modulating its stiffness in the sagittal plane. The Variable Stiffness Ankle unit (VSA) is mounted on a commercially available prosthetic foot. The stiffness of the foot is adjusted with a lightweight servo motor controlled wirelessly. The stiffness change is accomplished by moving the supports points on the glass fiber leaf spring of the VSA ankle unit. We described the design and characterized changes in ankle stiffness using a mechanical test bench. A novel method was used to capture mechanical test data using a six degree of freedom load cell, allowing us to contrast mechanical and biomechanical data. A transtibial unilateral amputee performed level ground walking on an instrumented treadmill. The VSA prosthetic foot exhibited ankle stiffness change in the mechanical test bench. Ankle stiffness changes were also confirmed during the biomechanical analysis. Future work will involve additional subjects. The VSA prosthetic foot could improve user satisfaction and help prosthetist to fine tune prosthetic feet during fittings.